1989
DOI: 10.1557/proc-176-583
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Pu(Vi) in Near-Neutral to Basic Solutions via Spectroscopy

Abstract: The high sensitivity technique of laser photoacoustic spectroscopy and optical absorption spectroscopy were utilized to investigate the hydrolysis of Pu(VI) in perchlorate media. Absorption bands attributed to the hydrolysis of Pu(VI) were characterized in the pH = 6–8 regime which is of most interest to the proposed repository site at Yucca Mountain. Evidence was presented that supported the assignment of the polynuclear species (640 nm species) reported previously \1] as (PuO2)3(OH)5+1. Some temperature-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The 638 nm species, once formed, does not dehydrolyze reversibly and takes at least weeks to completely dehydrolyze. We previously [3] suggested that this indicates the possible presence of polymerization, which may be affected by solution aging. Our data show that monomeric species are not important at concentrations as low as 10~4 M. Plutonyl appears to have a tendency toward the formation of polynuclear species that is comparable to the uranyl (UOl + ) species.…”
Section: Comparison Of Our Results To the Literaturementioning
confidence: 89%
See 3 more Smart Citations
“…The 638 nm species, once formed, does not dehydrolyze reversibly and takes at least weeks to completely dehydrolyze. We previously [3] suggested that this indicates the possible presence of polymerization, which may be affected by solution aging. Our data show that monomeric species are not important at concentrations as low as 10~4 M. Plutonyl appears to have a tendency toward the formation of polynuclear species that is comparable to the uranyl (UOl + ) species.…”
Section: Comparison Of Our Results To the Literaturementioning
confidence: 89%
“…The spectra obtained at higher pH were deconvoluted in the same manner as the spectrometric data. The generalized reaction for the hydrolysis of Pu(VI) is: qPuO| + + pH20 <-+ (Pu0 2 )q(0H)<, 2q ~p ) + + pH + (3) and the stability constant βρ^ is defined as…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cornerstone technique is pulsed-laser photoacoustic spectroscopy (PAS). This technique is rapidly gaining acceptance as the premiere method for determining actinide speciation in solution (Bennett et al, 1992;Berg et al, 1991a and b;Beitz et al, 1990;Okajima et al, 1990;Klenze and Kim, 1988;Beitz et al, 1988;Pollard et al, 1988;Eiswirth et al, 1985;Stumpe et al, 1984). The theoretical and experimental bases for the technique have been summarized in a number of review publications (Patel and Tam, 1981;Tam, 1986).…”
Section: Actinide Speciation: a Multifaceted Spectroscopic Approachmentioning
confidence: 99%